Caution as a response to scientific uncertainty: A groundwater game experiment - Ahn, Minwoo; Baldwin, Elizabeth; Girone, Dylan (Ubiquity Press, Ltd., 2024)
Understanding and managing uncertainty is critical for robust governance. In groundwater management, where collaborative, community-based governance is increasingly common, scientific uncertainty about hydrological conditions could pose challenges to effective and equitable resource management. This study bridges two literatures – collaborative governance and collective action – to examine whether scientific uncertainty about hydrologic conditions undermines the performance of groups that engage in collaborative governance of shared groundwater resources. We conducted a modified groundwater game experiment, based on Meinzen-Dick et al. (2016), where participants engage as resource users in a crop choice game over multiple rounds. But unlike the original game, where participants had full information about recharge rate, two treatments introduced scientific uncertainty in water recharge: uncertainty framed as a range of estimates about groundwater recharge, and uncertainty framed as competing hydrological models predicting different groundwater recharge rates. We also expand on the original game by exploring a wider range of outcomes that include not only sustainable resource use but also group earning and equitable distribution of earnings across players. Analyzing data from 30 group games, our findings suggest that scientific uncertainty can help safeguard shared groundwater resources by prompting users to exercise caution in the face of uncertain recharge rates. This effect was more consistent for the range of estimates treatment than for the competing hydrological models treatment. To unpack the mechanisms behind the experimental result, we also analyzed participants’ communications during the game to understand the strategies that collaborative groups use to cope with uncertainty. In the presence of scientific uncertainty, collaborative processes foster cautious behavior and protect shared resources.